High prevalence of HIV p24 antigen among HIV antibody negative prospective blood donors in Ile Ife, Nigeria (2016)
Blood transfusion service centers in Nigeria screen donated blood for markers of HIV infection using antibody- (Ab) based rapid test and in some centers, positives are re-tested using Ab-based ELISA. Paucity of data exists on p24 antigen prevalence among HIV Ab-negative donors in Nigeria. This study aims at detecting HIV p24 antigen among prospective blood donors in Osun State, Nigeria. Prospective blood donors negative for HIV antibodies using Determine test kit were re-tested using BIORAD GENSCREEN Ultra Ag-Ab ELISA kit, a fourth-generation ELISA kit that detects HIV antibodies/p24 antigen. Of the 169 HIV Abnegative prospective donors, 10 (5.9%) were positive for HIV antigen and 70% (7/10) of them were in the age range 18–30 years. Results of this study show that blood transfusion is still one of the major routes of HIV transmission in Nigeria and a higher proportion is among youth. Inclusion of p24 antigen testing into the blood donor screening will help reduce transfusion associated HIV in Nigeria if Nucleic Acid Testing (NAT) of all blood donor samples is not affordable; also, HIV enlightenment programs tailored toward youth may help reduce this rate among donors since more young people donate blood in low/middle income countries than in high-income countries.